2018
DOI: 10.2147/ott.s158868
|View full text |Cite
|
Sign up to set email alerts
|

Impact of RNA integrity and blood sample storage conditions on the gene expression analysis

Abstract: BackgroundThe reliability of RNA sequencing (RNA-seq) output is affected by the quality of RNAs, which is in turn dependent on the quality of samples. Therefore, the purposes of this study were to reconsider the threshold of the RNA integrity number (RIN) and propose a simple and efficient storage scheme of blood samples for RNA-seq.Patients and methodsThe RNAs were extracted from blood samples that were stored at different conditions and used for sequencing. The bioinformatic analyses were performed to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 17 publications
4
25
0
2
Order By: Relevance
“…Next-generation sequencing is typically performed on high quality RNA (RIN > 7), when possible [ 28 ]. However, clinical samples, particularly human neutrophils that contain high levels of endonucleases as part of the host defense response to bacteria, rarely produce RNA without any degree of degradation [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Next-generation sequencing is typically performed on high quality RNA (RIN > 7), when possible [ 28 ]. However, clinical samples, particularly human neutrophils that contain high levels of endonucleases as part of the host defense response to bacteria, rarely produce RNA without any degree of degradation [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Next-generation sequencing is typically performed on high quality RNA (RIN>7), when possible. 28 However, clinical samples, particularly human neutrophils that contain high levels of endonucleases as part of the host defense response to bacteria, rarely produce RNA without any degree of degradation. 29 Between…”
Section: Differential Expression Analysis and Data Explorationmentioning
confidence: 99%
“…In general, it is suggested that RNAs with RINs over 7 are preferred for downstream applications such as NGS. Against this general guideline, some publications have stated that RNAs with an RIN around 5 can also be used without causing any signi cant bias over high-quality RNA [13]. With reference to these thresholds of RIN 5-7, RNAs were selected for RNA sequencing using the Ion AmpliSeq platform (Thermo Fisher Scienti c).…”
Section: Rna Sequencing and Analysismentioning
confidence: 99%